PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN BERBASIS APLIKASI ANDROID DALAM MENDUKUNG KEGIATAN BELAJAR DARI RUMAH DI MASA PANDEMI COVID-19 - Rudy Ntelok; Yohannes Marryono Jamun; Rudolof Ngalu (Unika Santu Paulus Ruteng, 2021)
The Covid-19 pandemic that has hit the world including Indonesia has had a serious impact on all sectors of human life including the education sector. Everyone is forced to stay at home to break the transmission of Covid-19. Public facilities such as schools were closed to prevent the spread of Covid-19. The closure of schools resulted in learning activities moving to a distance learning system by utilizing internet (online) facilities on an untested and unprecedented scale. The aims of this community service activity is to train teachers to be able to make learning videos to support and meet the learning needs of students during the Covid-19 pandemic by utilizing android applications on the teacher's mobile device. The implementation of this PkM activity is carried out in three stages, namely 1) the socialization stage, 2) the simulation stage, and 3) the training and mentoring stage. The results of the activity showed that after training and mentoring, the teacher was able to make learning videos. With instructional videos, teachers and students are helped in implementing learning activities during this pandemic.